Does More Sedentary Time Associate With Higher Risks for Sleep Disorder Among Adolescents? A Pooled Analysis - Zhang, Yanjie; Chen, Sitong; Wang, Chengyao; Zhang, Xiaoyi; Zou, Liye; Chi, Xinli; Jiao, Can (Frontiers in Pediatrics, 2021)
Purpose: To investigate the association between sedentary behavior and anxiety-induced sleep disorder at global perspective. Methods: A total of 25,4924 adolescents (mean age: 14.45±1.42 years; 52.8% girls) participated in the Global School-Based Student Health Survey were included for analysis. Self-reported questionnaires assessed anxiety-induced sleep disorder and sedentary behavior. Multivariable logistic regression analysis and countrywide meta-analysis were used for investigating the association between sedentary behavior and anxiety-included sleep disorder. Results: The results showed that sedentary time was linearly associated with higher OR of anxiety-related sleep disorder in adolescents across the countries, and that 8 hours or more per day increased the OR in 2.17 times. Countrywide meta-analysis showed that 8 hours or more per day of sedentary behavior yielded a OR=1.40 (95% CI=1.34-1.46) of anxiety-induced sleep disorder. Moreover, the association between sedentary behavior and sleep-anxiety existed significantly in adolescents over the age of 11 years regardless of sex. Conclusions: The findings from this study suggests that as sedentary behavior increases, sleep disorders also increase, independently of sex among adolescents. Effective preventive strategies are needed to be taken to decrease sedentary behavior that could be used to improve mental health and sleep quality among adolescents.